Wording in the area of mobility and physical activity—the challenge of perception for researchers and older persons Formulierungen im Bereich Mobilität und körperliche Aktivität – die Herausforderung der Wahrnehmung für Forscher und ältere Menschen - Freiberger, Ellen; Notthoff, Nanna (German Journal of Exercise and Sport Research, 2021)
When promoting physical activity (PA) to older persons, perceived wording is of importance and mostly not congruent with the scientific approach. The differentiation within physical activity subcategories is often unnoticed by other health professionals as well as by older persons. Especially, the subcategory of exercise as a planned, structured, repetitive program is often used interchangeably with PA. This short communication addresses the different perceptions in wording between health care professionals, sport scientists, and lay older persons with the goal to enhance the awareness of wording for professionals, which is a prerequisite for designing appropriate messages.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Aging; Mobility; Perception; Physical activity; Walking